2017
DOI: 10.1002/cjce.23085
|View full text |Cite
|
Sign up to set email alerts
|

NMSBA produced from NMST under the catalysis of supported H3PW12O40 and Co/Mn/Br catalytic system

Abstract: The commercial production of 2‐nitro‐4‐methylsulphonylbenzoic acid (NMSBA) is oxidizing 2‐nitro‐4‐methylsulphonyltoluene (NMST) by nitric acid catalyzed with V2O5. A heterogeneous catalytic system composed of phosphotungstic acid supported on activated carbon, Co, Mn, and Br is used to catalyze the production of NMSBA from NMST by oxygen in this paper. The experiments show that the heterogeneous catalytic system composed of HPW@C, Co, Mn, and Br is capable of speeding up the oxidation of NMST to NMSBA by oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Long et al [ 10 ] put forward a homogeneous quaternary system composed of Co/Mn/Br/H 3 PW 12 O 40 to catalyze the oxidation of NMST to NMSBA by air in acetic acid at 215°C and 3.0 MPa. He et al [ 11 ] decreased the usage of H 3 PW 12 O 40 , accelerated NMST oxidation, and increased NMSBA yield with a heterogeneous catalytic system by immobilizing H 3 PW 12 O 40 on activated carbon. Wen et al [ 12 ] improved the catalytic capability of H 3 PW 12 O 4 @C by modifying the carbon with a ZnCl 2 solution.…”
Section: Introductionmentioning
confidence: 99%
“…Long et al [ 10 ] put forward a homogeneous quaternary system composed of Co/Mn/Br/H 3 PW 12 O 40 to catalyze the oxidation of NMST to NMSBA by air in acetic acid at 215°C and 3.0 MPa. He et al [ 11 ] decreased the usage of H 3 PW 12 O 40 , accelerated NMST oxidation, and increased NMSBA yield with a heterogeneous catalytic system by immobilizing H 3 PW 12 O 40 on activated carbon. Wen et al [ 12 ] improved the catalytic capability of H 3 PW 12 O 4 @C by modifying the carbon with a ZnCl 2 solution.…”
Section: Introductionmentioning
confidence: 99%
“…Long et al 8 obtained a NMSBA yield of over 80% at 215 °C and 3.0 MPa by oxidizing NMST with air for 2.5 h in acetic acid under the aid of the multi component homogeneous catalytic system composed of Co-Mn-Br-phosphotungstic acid. He et al 9 constructed the heterogeneous catalytic system of Co-Mn-Br-phosphotungstic acid@CAC by supporting phosphotungstic acid on commercial activated carbon (CAC) to speed up the oxidation of NMST to NMSBA. It was found that the amount of phosphotungstic acid was greatly reduced and the NMSBA yield was improved conspicuously.…”
Section: Introductionmentioning
confidence: 99%